A literatura nativa nas obras de Kaka Werá Jecupé: produções, resistências e culturas dos povos indígenas - Oliveira, Elisa Faria de (2023)
The research in question has as its theme the analysis of the literary productions of indigenous peoples, taking into account the resistance and cultures involved within these writing processes. Thus, analyzing the works of Kaka Jecupé, Todas as Vezes que Dissemos Adeus (2002), A Terra dos Mil Povos (1998), O Trovão e o Vento (2016) and Tupã Tenondé (2001), with the aim of structuring these creations for the bases to be studied. Taking into account that the elaboration of these books is something contemporary and it is necessary to elaborate theories for a better designation. Therefore, the term “native literature”, generated by Olívio Jekupé (2021) will be the term used in naming the writings produced and elaborated by indigenous people, which was conceived with this focus, to title something new, in which the origins and essences of the ideas and interests involved. Jekupé (2021) points out that the need for an expression comes from the fact that it is something recent and that does not fit into existing concepts and that is what this research seeks, to assist in this theoretical basis on these productions. Therefore, it is necessary to question cultural elements and the struggles involved with the indigenous peoples of Brazil and the resistance that encompasses the writing of these subjects. In addition, for the development of the research in question, the use of decolonial methodologies supported the perceptions of the actions and movements of indigenous peoples in society due to the ideals that Mignolo (2017) points out about the legacies of the colonization of current practices. Thus, the violence suffered more than 500 years ago remains with these communities, however, they have been re-signified to the currently accepted molds and all these elements need to be covered and captured for the analysis of indigenous literary productions. Because using a resource from the colonizers for the realization and expansion of other cultures that were subjected to prohibition processes is the result of a long process of struggle and resistance of these subjects that interfere in everyday practices and in their productions.